2021
DOI: 10.1002/brb3.2200
|View full text |Cite
|
Sign up to set email alerts
|

Resting‐state functional connectivity in patients with a complex PTSD or complex dissociative disorder before and after inpatient trauma treatment

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 77 publications
(162 reference statements)
2
4
0
Order By: Relevance
“…Given this, decreased functional connectivity between the PCC and isthmus could reflect inefficient or slowed synchronization between these regions of the brain that are critical for sensory integration, consciousness, and the physical sense of self and place. Our finding of decreased DMN connectivity is consistent with at least one EEG study of pretreatment dissociative conditions, with data suggesting increased DMN connectivity following treatment (Schlumpf et al, 2021). It is important to note that we studied trait but not state dissociation, thus this functional connectivity correlate could represent a vulnerability to derealization/depersonalization rather than (or in addition to) the neurobiology of an active dissociative state.…”
Section: Discussionsupporting
confidence: 89%
“…Given this, decreased functional connectivity between the PCC and isthmus could reflect inefficient or slowed synchronization between these regions of the brain that are critical for sensory integration, consciousness, and the physical sense of self and place. Our finding of decreased DMN connectivity is consistent with at least one EEG study of pretreatment dissociative conditions, with data suggesting increased DMN connectivity following treatment (Schlumpf et al, 2021). It is important to note that we studied trait but not state dissociation, thus this functional connectivity correlate could represent a vulnerability to derealization/depersonalization rather than (or in addition to) the neurobiology of an active dissociative state.…”
Section: Discussionsupporting
confidence: 89%
“…In this line of reasoning, a strengthening in the autobiographical memory network in response to visual cues could also reflect that treatment may have helped the patients as ANP to experience and see more what is self-relevant and of affective significance to them. This interpretation is in accordance with a resting-state functional connectivity study suggesting an increased ability in ANPs to engage in self-related thinking across a phase-oriented inpatient treatment ( 80 ) and is further supported by the growing body of evidence that relates dissociation to a reduce capacity for self-reference ( 81 83 ). The increased functional coupling among occipital areas in the network involved in the execution of cognitive reappraisal suggests as well-that the patients experienced and perceived unpleasant pictures more intensely following treatment while they managed to reduce their emotional responses to these cues.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, a continuation of treatment is required. Previous findings of relationships between alterations in questionnaire data and neural changes across treatment are inconsistent ( 27 , 80 , 87 90 ). In the present study, network changes were neither associated with self-reported symptom reduction, nor with improvement in emotion regulation capacities.…”
Section: Discussionmentioning
confidence: 89%
“…This might provide the field with more insight on the effect of timing of the exposure to the potential traumatic event. We would further like to mention that next to investigations using rs-fMRI the field has recently also studied rs-FC in individuals with PTSD using EEG, which might complement several methodological difficulties associated with rs-fMRI ( Schlumpf et al, 2021 , Heinrich et al, 2014 , Mutschler et al, 2014 ). Future investigation might therefore benefit from using a multimodal approach in studying rs-FC.…”
Section: Discussionmentioning
confidence: 99%